A Practical Example Using VR in the Assessment of Brain Injury - Davies, R. C.; Johansson, G; Boschian, K; Lindé, A.; Minör, U.; Sonesson, B. (International Journal of Virtual Reality, 1999)
Virtual Reality (VR) as a complementary tool for medical practitioners in the assessment and rehabilitation of people who have suffered a traumatic brain injury (TBI) is discussed. A pilot-study has been undertaken on a prototype VR assessment tool. The design involved nine occupational therapists with expertise in the care of traumatic brain injured patients and one (computer experienced) patient. The aim was to begin a dialogue and to ascertain the potential of a VR system. A common method for occupational therapists to assess function and ability is to ask a patient to brew coffee. From the performance of such a task, an individual's "functional signature" can be determined. The prototype was built using Superscape, a personal computer based VR system, to be close to the real coffee making task, including effects of making mistakes, realistic graphics and sound effects. The world was designed to be as easy to use and intuitive as possible, though problems of mental abstraction level, transfer of training and realistic interaction have yet to be resolved. The comments from the test participants have highlighted problem areas, given positive insight and pointed out other scenarios where VR may be of use in the rehabilitation of people with a traumatic brain injury.